Spatial variability in the diagnosis of nutritional status in the papaya - Lima, Julião; Alves, Danielle; Coelho, Ruimário; Sturião, Walas; Silva, Samuel (Revista Ciência Agronômica, 2016)
Leaf analysis is widely used to study the nutritional status of plants, based on the fact of there being a direct correlation between rate of growth and the nutrient levels in leaf tissue. This study was carried out on a commercial crop of Golden THB papaya, in the north of the State of Espirito Santo, Brazil, to determine the spatial variability of nutrients in the petiole of leaf samples collected when carrying out sexing in a regular grid of 129 georeferenced points. Harvesting was carried out manually 270-365 days after transplanting. All the characteristics displayed a strong spatial dependence, the spherical and exponential semivariograms being adjusted for the data. The greatest and smallest ranges were found for the micronutrients Mn and Zn respectively. Mean productivity was considered to be low at 13.6 Mg ha-1. Geostatistical analysis of the data aided in the preparation of thematic maps showing the different areas of productivity and foliar application of fertiliser in the papaya. However, the largest regions in the area were displayed by those classes which included the mean value for an attribute, indicating the use of the mean values in the recommendation of foliar fertilisation, with the exception of P and K.